Analysis of the Mechanism of Smart Sports Services in School Physical Education and Student Physical Health - Liu, Yongsen; Zhang, Mufan; Ji, Bin (Quality in Sport, 2025)
With the rapid development of information technology, smart sports have emerged as a new form of support and service for school physical education and student physical health. This study adopts literature review and logical analysis methods to explore the connotations, categories, basic elements, and mechanisms of smart sports services for school physical education and student physical health. The study points out that: (1) Smart sports services refer to efforts aimed at improving the quality and effectiveness of school physical education through the application of information technology, achieving the organic integration of student physical health and school physical education, and providing personalized and precise sports services. (2) Smart sports services in school physical education include four categories: data collection and analysis, teaching assistance and management, sports resource sharing and exchange, and health management and services. (3) The basic elements of smart sports services for school physical education and student physical health include policies, technology, and the practical needs of school physical education development, where policies provide support and guidance for smart sports services, technology serves as the foundation of these services, and the practical needs of school physical education development act as the motivation for the services. (4) The process of smart sports services for school physical education and student physical health involves data collection and analysis, personalized diagnosis and customized plans, service tracking and monitoring, personalized feedback and incentives, and effect evaluation and improvement. (5) The inherent mechanism of the service is to facilitate convenient and intelligent school physical education management, promote accurate and enjoyable sports teaching, ensure fairness and efficiency in school physical education exams, and empower students’ physical exercise to be personalized and proactive.